O indivíduo diante de Deus: a existência como um projeto a ser efetivado - Sanches, Cleber (2023)
The thesis "The individual before God: Existence as a project to be realized" seeks to explore the existential thought of Sören Kierkegaard, from a Christian perspective, in which human existence is seen as a project that must be realized in the individual's relationship with God. To this end, the thesis is divided into four chapters. Firstly, a reflection will be established on the personal life of the Danish author, the historical context in which he lived, the main works he wrote, and how Hegel's philosophy influenced his thinking. The possibilities of human existence will be discussed. Kierkegaard argues that human existence is not just a fact, but a possibility that opens up before each individual. He emphasizes that each person has the responsibility to choose and realize their existence in a unique and authentic way by ultimately choosing themselves. The three stages of existence will be presented, which represent the different ways in which the individual relates to themselves, to others, and to God. They are the aesthetic stage, the ethical stage, and the religious stage. Each of these stages is marked by different values and ideas, and the objective is to understand how the individual, perceiving themselves, fails when trying to give meaning to life by themselves, outside of the relationship with God. The thesis focuses on the figure of Christ as an existential model and on the reduplication of dialectics. Kierkegaard argues that the figure of Christ is the maximum expression of authenticity in the individual's relationship with God, and that the reduplication of dialectics is the way in which the individual can realize their existence through the relationship with the divine